Carabidae from Pitfall Traps, arable fields in lower saxony, June 2020 - Mersmann, Frederik (PANGAEA, 2021)
Data from 60 Pitfall Traps, from lower Saxony (districts Diepholz und Nienburg south of Bremen). Collected from 06.06.2020 - 12.06.2020. All Individuals of Carabidae are determined to species level. 3 Traps were placed each on a field margin with winter-grain and on neighbouring fallows. 10 fields were sampled. The Data was collected and analysed for a Bachelor Thesis. The analysis via DCA and NMDS each showed significantly different communities on fallows and field margins. An important Factor for the occurence of species appears to be the location of the field (probably due to neighbouring areas, soil, history of usage,... ). The Main Part of the Thesis was a botanical analysis. Botanical and zoological Data both underline the importance of a diverse structure in agricultural landscapes for biodiversity and food security due to stable ecosystems.
Keywords: Carabidae; Ecology & Environment; Pitfall Trap counts; Zoology